Aluminum alloy composite plate and preparation method thereof
By optimizing the element content and process processing of aluminum alloy composite plates, a high-strength, corrosion-resistant aluminum alloy composite plate is formed, which solves the problem of insufficient performance of aluminum alloy composite materials in offshore wind turbines, and achieves better mechanics and sag resistance performance.
Patent Information
- Application Number
- CN202411294971.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-14
AI Technical Summary
Existing aluminum alloy composite materials are difficult to meet the mechanical properties, sag resistance and corrosion resistance requirements for long-term operation in offshore wind turbines, especially in harsh environments and complex stress conditions.
Using a specific aluminum alloy composite plate structural design, including a core layer and a laminated leather layer, the AlFeMnSi-based compounds and Fine diffuse phases improve strength and corrosion resistance, and regulate grain structure through preheating and annealing processes.
It significantly improves the mechanical properties, sag resistance and corrosion resistance of aluminum alloy composite plates, meets the long-term operation needs of offshore wind turbines, avoids melting and collapse problems during brazing, and reduces the corrosion potential of the diffusion layer. Difference.
Smart Images

Figure CN119141973A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aluminum alloys, and in particular to an aluminum alloy composite plate and a preparation method thereof. Background Art
[0002] Aluminum alloys have been widely used in the field of heat exchangers due to their high specific strength, excellent heat transfer performance, abundant reserves and low cost. The full aluminumization of heat exchangers has become an inevitable trend in its development.
[0003] In recent years, the wind power market has maintained a sustained growth trend, and the heat exchangers for wind power generation are mainly made of vacuum brazed aluminum. Offshore wind turbines work in a marine climate environment, have a long service life, and are subject to harsh environmental conditions and complex stress changes during operation. Therefore, higher requirements are placed on the mechanical properties and corrosion resistance of brazed composite materials.
[0004] At present, adjusting the ratio of aluminum alloy components is the main way to improve the strength of aluminum alloy composite materials for brazing. However, while the addition of alloy elements improves the strength, it will also have a certain impact on the corrosion resistance of brazing composite materials.
[0005] The Chinese patent with patent application announcement number CN110947762B provides a core alloy composition and preparation method of a 308 aluminum alloy three-layer composite plate for vacuum brazing, which adopts hot rolling, cold rolling and finished product annealing processes to solve the problem of low strength before and after brazing of conventional 3003 aluminum alloy composite plates and low pressure bearing value of brazed products. However, the content range of Si, Fe, Cu, Mn, Mg, Zn, Ti, (Mn+Fe) and other elements in this patent is relatively wide, and the low content of Mn element leads to weak dispersion strengthening effect, while the high content of Mg element is prone to cause intergranular corrosion.
[0006] The Chinese patent application with the patent application publication number CN115771311A provides an aluminum alloy composite material for brazing and a manufacturing method thereof, wherein the content range of Si, Cu, Mn, Mg, Fe, Sr, Zn, Ti, Zr, and Cr in the core alloy is relatively wide, and the content of Si is relatively high. A high content of Si element is prone to the risk of melting and collapse of the alloy during the brazing process, and a high content of Si element is prone to enrichment at the grain boundary, and a low Si concentration area is formed near the grain boundary, which is prone to cause intergranular corrosion.
[0007] Therefore, there is an urgent need to develop an aluminum alloy composite material with good mechanical properties, anti-sagging properties and corrosion resistance to meet the performance requirements of brazing composite materials posed by stress changes and environmental conditions during the operation of offshore wind turbines. Summary of the invention
[0008] The main purpose of the present invention is to provide an aluminum alloy composite plate and a preparation method thereof, so as to solve the problem that the mechanical properties, anti-sagging properties and corrosion resistance of aluminum alloy composite materials for brazing in the prior art are difficult to meet the long-term operation requirements of offshore wind turbines.
[0009] In order to achieve the above-mentioned object, according to one aspect of the present invention, there is provided an aluminum alloy composite plate, which includes a core material layer and a skin material layer stacked on two opposite surfaces of the core material layer; the core material layer includes the following elements by mass percentage: the core material layer includes the following elements by mass percentage: 0.2-0.6% Si element, 0.3-0.6% Cu element, 0.1-0.3% Mg element, 0.2-0.6% Fe element and 1.4-1.8% Mn element, the sum of the mass contents of Ti element and Zr element is 0.15-0.4%, the total content of inevitable impurities is ≤0.15%, the content of a single impurity is <0.05%, and the balance is Al element; by mass percentage, Each skin material layer includes the following elements: 9.5-12.0% Si element, 0.6-1.0% Fe element, 1.4-1.8% Mg element, 0.05-0.25% Zn element and 0.08-0.2% Bi element, the total content of inevitable impurities is ≤0.15%, the content of single impurity is <0.05%, and the balance is Al element; the potential difference between the diffusion layer and the skin material layer formed after brazing of the aluminum alloy composite plate is ≥450mV; before brazing of the aluminum alloy composite plate, the tensile strength of the aluminum alloy composite plate is ≥220MPa, the yield strength is ≥195MPa, and the elongation is ≥5.5%; after brazing of the aluminum alloy composite plate, the yield strength of the aluminum alloy composite plate is ≥64.7MPa, and the anti-sagging value is ≤4mm.
[0010] Furthermore, in terms of mass percentage, the core material layer comprises the following elements: 0.3-0.5% Si, 0.4-0.6% Cu, 0.15-0.25% Mg, 0.2-0.4% Fe and 1.5-1.7% Mn, the sum of the mass contents of Ti and Zr is 0.2-0.3%, the total content of inevitable impurities is ≤0.15%, the content of a single impurity is <0.05%, and the balance is Al; in terms of mass percentage, the skin material layers comprise the following elements: 10-11.5% Si, 0.6-0.8% Fe, 1.45-1.65% Mg, 0.1-0.2% Zn and 0.1-0.15% Bi, the total content of inevitable impurities is ≤0.15%, the content of a single impurity is <0.05%, and the balance is Al.
[0011] Furthermore, in the core material layer, the mass ratio of the Mn element to the Fe element is 4 to 6:1, and / or the mass ratio of the Mg element to the Si element is 3 to 8:10.
[0012] Furthermore, the size of the AlMnSi dispersed phase in the core material layer is 100-200 nm; the size of the Fe-containing second phase in the core material layer is controlled to be 1-10 μm, and the area ratio of the Fe-containing second phase in the core material layer is 1.6-2.58%.
[0013] According to another aspect of the present invention, there is provided a method for preparing the above-mentioned aluminum alloy composite plate, the preparation method comprising: step S1, heating and rolling the first skin material ingot, the core material ingot and the second skin material ingot independently in sequence to obtain the first skin material ingot layer, the core material ingot layer and the second skin material ingot layer, stacking the first skin material ingot layer, the core material ingot layer and the second skin material ingot layer in sequence and performing composite rolling treatment to obtain a composite billet; step S2, preheating the composite billet in sequence, performing hot rough rolling and hot finish rolling to obtain a hot-rolled billet; and step S3, cold rolling the hot-rolled billet in sequence, intermediate annealing and two cold rolling. The aluminum alloy composite plate is obtained by cold rolling for the first time; wherein, the preheating treatment process includes: heating the composite billet to 460-490°C at 30-80°C / h and then keeping it warm for 1-6h; the intermediate annealing is direct annealing of the billet after the first cold rolling or continuous intermediate annealing; the direct annealing process includes: heating the billet after the first cold rolling to 380-460°C at 20-90°C / h and then keeping it warm for 0.5-3h; the continuous intermediate annealing process includes: heating the billet after the first cold rolling to 400-480°C at 30-120°C / s and then keeping it warm for 60-240s, and then cooling it to below 100°C at 50-250°C / s.
[0014] Furthermore, the preheating process includes: heating the composite blank to 460-490° C. at 40-60° C. / h and then keeping the temperature for 2-4 hours.
[0015] Further, the direct annealing process includes: heating the blank after the first cold rolling to 400-460°C at 50-80°C / h and then keeping it warm for 0.5-3h; and / or, the continuous intermediate annealing process includes: heating the blank after the first cold rolling to 440-480°C at 40-100°C / s and then keeping it warm for 60-240s, and then cooling it to below 100°C at 100-200°C / s.
[0016] Furthermore, the total processing rate of the first cold rolling is 80-90%, and / or the total processing rate of the second cold rolling is 10-25%.
[0017] Furthermore, the above-mentioned step S1 also includes: independently melting, sawing and milling the skin material alloy and the core material alloy in sequence to obtain skin material ingots and core material ingots respectively; wherein, during the melting and casting process, the skin material alloy is modified by antimony; and / or the single-sided milling amount of the milling surface is 15 to 20 mm, and the difference between the longitudinal and transverse milling amounts of the milling surface is ≤2 mm.
[0018] Furthermore, in the above step S1, a steel belt is used to fix the stacked structure after the first skin material ingot layer, the core material ingot layer and the second skin material ingot layer are stacked in sequence for composite rolling treatment; the thickness ratio of the first skin material ingot layer, the core material ingot layer and the second skin material ingot layer is 1:8~10:1; and / or, the widths of the first skin material ingot layer and the second skin material ingot layer are each independently greater than the width of the core material ingot layer, and the tolerance of the difference between the widths of the first skin material ingot layer and the second skin material ingot layer and the width of the core material ingot layer is each independently 10~40mm.
[0019] By applying the technical solution of the present invention, the aluminum alloy composite plate of the present application includes a core material layer and a skin material layer stacked on both sides of the core material layer, and the structural design can optimize the comprehensive performance of the aluminum alloy composite plate. In the core material layer: the added Si element, Fe element and Mn element can form AlFeMnSi series compounds, thereby playing a role of dispersion strengthening. At the same time, the Si element, Fe element and Mn element are solid-dissolved in the matrix and can improve the strength of the aluminum alloy composite plate through solid solution strengthening, and controlling the content of the Si element within the above range can not only improve the strengthening effect, but also avoid the problems of melting and collapse of the aluminum alloy composite plate during brazing and intergranular corrosion. Adding Mn elements and Fe elements can improve the forming performance and strength of the aluminum alloy composite plate. At the same time, controlling the content of the Fe element within the above range can improve the forming performance and corrosion resistance of the aluminum alloy composite plate. Adding Mg elements, Si elements and Cu elements helps to quickly cool the aluminum alloy composite plate after brazing and place it at room temperature to cause natural aging, thereby producing fine, dispersed Mg2Si phases and Al2CuMg phases. At the same time, a higher strength aluminum alloy composite plate can be obtained through the synergistic effect of solid solution strengthening and dispersion strengthening. The solid solution strengthening effect of adding Ti elements and Zr elements can improve the strength of the alloy, and at the same time, promote the generation of fine dispersed Al3Ti precipitation phase and Al3Zr precipitation phase, thereby further improving the strength of the alloy. In addition, the addition of Ti elements and Zr elements can promote the formation of coarse and long strip grains during brazing of aluminum alloy composite plates, thereby improving the anti-sagging performance of aluminum alloy composite plates; controlling the content of Ti elements in the above range can change the corrosion potential of the alloy, thereby improving the corrosion resistance of aluminum alloy composite plates. In each skin material layer: the added Bi element can not only increase the wettability of Si liquid phase to the surface of aluminum alloy material, but also promote the fluidity of Si liquid phase, thereby improving the welding performance of aluminum alloy composite plates. The low content of Bi element cannot achieve the performance of the above aluminum alloy composite plate. The high content of Bi element not only has limited effect on further improvement, but also leads to increased cost. Therefore, controlling the content of Bi element in the above range can take into account both effect and cost. Controlling the content of Zn element within the above range can reduce the corrosion potential of each skin material layer, so that the potential difference between the diffusion layer and the skin material layer formed after brazing of the aluminum alloy composite plate is ≥450mV, and the potential distribution of the diffusion layer is uniform and the driving force of galvanic corrosion is reduced, thereby improving the corrosion resistance of the aluminum alloy composite plate. Among them, the diffusion layer is a tissue layer formed by the mutual diffusion of alloy elements under the action of concentration gradient during the brazing process between the skin material and the core material. By coordinating and optimizing the above elements in the core material layer and each skin material layer, the mechanical properties, anti-sagging performance and corrosion resistance of the aluminum alloy composite plate can be comprehensively improved, so as to better meet the requirements of long-term operation of offshore wind turbines. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0021] Figure 1 The morphology of the Fe-containing second phase in the core material layer of the aluminum alloy composite plate in Example 1 of the present application is shown;
[0022] Figure 2 The morphology of the AlMnSi phase of the aluminum alloy composite plate in Example 1 of the present application is shown;
[0023] Figure 3 The figure shows the grain morphology of the aluminum alloy composite plate after brazing in Example 1 of the present application;
[0024] Figure 4 The morphology of the Fe-containing second phase in the core material layer of the aluminum alloy composite plate in Comparative Example 1 of the present application is shown;
[0025] Figure 5 The morphology of the AlMnSi phase of the aluminum alloy composite plate in Comparative Example 1 of the present application is shown;
[0026] Figure 6 The grain morphology of the aluminum alloy composite plate after brazing in Comparative Example 1 of the present application is shown. DETAILED DESCRIPTION
[0027] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0028] As analyzed in the background technology of this application, there is a problem in the prior art that the mechanical properties, anti-sagging properties and corrosion resistance of aluminum alloy composite materials for brazing are difficult to meet the long-term operation requirements of offshore wind turbines. In order to solve the above problems, this application provides an aluminum alloy composite plate and a preparation method thereof.
[0029] In a typical embodiment of the present application, an aluminum alloy composite plate is provided, which includes a core material layer and a skin material layer stacked on two opposite surfaces of the core material layer; in terms of mass percentage, the core material layer includes the following elements: in terms of mass percentage, the core material layer includes the following elements: 0.2-0.6% Si element, 0.3-0.6% Cu element, 0.1-0.3% Mg element, 0.2-0.6% Fe element and 1.4-1.8% Mn element, the sum of the mass contents of Ti element and Zr element is 0.15-0.4%, the total content of unavoidable impurities is ≤0.15%, the content of a single impurity is <0.05%, and the balance is Al element; in terms of mass percentage, each skin ... The material layer includes the following elements: 9.5-12.0% Si element, 0.6-1.0% Fe element, 1.4-1.8% Mg element, 0.05-0.25% Zn element and 0.08-0.2% Bi element, the total content of inevitable impurities is ≤0.15%, the content of single impurity is <0.05%, and the balance is Al element; the potential difference between the diffusion layer and the skin material layer formed after brazing of the aluminum alloy composite plate is ≥450mV; before brazing of the aluminum alloy composite plate, the tensile strength of the aluminum alloy composite plate is ≥220MPa, the yield strength is ≥195MPa, and the elongation is ≥5.5%; after brazing of the aluminum alloy composite plate, the yield strength of the aluminum alloy composite plate is ≥64.7MPa, and the anti-sagging value is ≤4mm.
[0030] The aluminum alloy composite plate of the present application includes a core material layer and a skin material layer stacked on both sides of the core material layer. The structural design can optimize the comprehensive performance of the aluminum alloy composite plate. In the core material layer: the added Si element, Fe element and Mn element can form AlFeMnSi series compounds, thereby playing a role in dispersion strengthening. At the same time, the Si element, Fe element and Mn element are solid-dissolved in the matrix and can improve the strength of the aluminum alloy composite plate through solid solution strengthening, and the content of the Si element is controlled within the above range, which can not only improve the strengthening effect, but also avoid the problems of melting and collapse of the aluminum alloy composite plate during brazing and intergranular corrosion. Adding Mn and Fe elements can improve the forming performance and strength of the aluminum alloy composite plate. At the same time, controlling the content of the Fe element within the above range can improve the forming performance and corrosion resistance of the aluminum alloy composite plate. Adding Mg, Si and Cu elements helps to quickly cool the aluminum alloy composite plate after brazing and place it at room temperature to enable natural aging, thereby producing fine, dispersed Mg2Si phases and Al2CuMg phases. At the same time, a higher strength aluminum alloy composite plate can be obtained through the synergistic effect of solid solution strengthening and dispersion strengthening. The solid solution strengthening effect of adding Ti elements and Zr elements can improve the strength of the alloy, and at the same time, promote the generation of fine dispersed Al3Ti precipitation phase and Al3Zr precipitation phase, thereby further improving the strength of the alloy. In addition, the addition of Ti elements and Zr elements can promote the formation of coarse and long strip grains during brazing of aluminum alloy composite plates, thereby improving the anti-sagging performance of aluminum alloy composite plates; and controlling the content of Ti elements in the above range can change the corrosion potential of the alloy, thereby improving the corrosion resistance of aluminum alloy composite plates. In each skin material layer: the added Bi element can not only increase the wettability of Si liquid phase to the surface of aluminum alloy material, but also promote the fluidity of Si liquid phase, thereby improving the welding performance of aluminum alloy composite plates. The low content of Bi element cannot achieve the performance of the above aluminum alloy composite plate, and the high content of Bi element not only has limited effect on further improvement, but also leads to increased cost. Therefore, controlling the content of Bi element in the above range can take into account both effect and cost. Controlling the content of Zn element within the above range can reduce the corrosion potential of each skin material layer, so that the potential difference between the diffusion layer and the skin material layer formed after brazing of the aluminum alloy composite plate is ≥450mV, and the potential distribution of the diffusion layer is uniform and the driving force of galvanic corrosion is reduced, thereby improving the corrosion resistance of the aluminum alloy composite plate. Among them, the diffusion layer is a tissue layer formed by the mutual diffusion of alloy elements under the action of concentration gradient during the brazing process between the skin material and the core material. By coordinating and optimizing the above elements in the core material layer and each skin material layer, the mechanical properties, anti-sagging performance and corrosion resistance of the aluminum alloy composite plate can be comprehensively improved, so as to better meet the requirements of long-term operation of offshore wind turbines.
[0031] In order to further improve the synergistic effect between the core material layer and each skin material layer, thereby optimizing the mechanical properties, anti-sagging performance and corrosion resistance of the aluminum alloy composite plate, in one embodiment of the present application, in order to further improve the synergistic effect between the elements, the core material layer preferably includes the following elements, in terms of mass percentage: 0.3-0.5% Si element, 0.4-0.6% Cu element, 0.15-0.25% Mg element, 0.2-0.4% Fe element and 1.5-1.7% Mn element, Ti element and Zr element. The sum of the mass contents is 0.2-0.3%, the total content of inevitable impurities is ≤0.15%, the content of a single impurity is <0.05%, and the balance is Al element; in terms of mass percentage, each skin material layer includes the following elements: 10-11.5% Si element, 0.6-0.8% Fe element, 1.45-1.65% Mg element, 0.1-0.2% Zn element and 0.1-0.15% Bi element, the total content of inevitable impurities is ≤0.15%, the content of a single impurity is <0.05%, and the balance is Al element.
[0032] In one embodiment of the present application, in the core material layer, the mass ratio of the Mn element to the Fe element is 4 to 6:1, and / or the mass ratio of the Mg element to the Si element is 3 to 8:10.
[0033] In the core material layer, it is preferred to control the mass ratio of the Mn element to the Fe element within the above range, which helps to improve the synergistic effect of the Mn element and the Fe element, thereby helping to further regulate the content of the AlFeMnSi series compound formed by Mn, Fe and Si, reduce the formation of coarse Fe-containing phases, and thus improve the corrosion resistance of the aluminum alloy composite plate. It is preferred to control the mass ratio of the Mg element to the Si element within the above range, which helps to enhance the synergistic effect of the Mg element and the Si element, thereby helping to form a fine Mg2Si phase, and further helping to improve the strength of the aluminum alloy composite material.
[0034] In one embodiment of the present application, the size of the AlMnSi phase in the core material layer is 100-200 nm; the size of the Fe-containing second phase in the core material layer is 1-10 μm, and the area ratio of the Fe-containing second phase in the core material layer is 1.6-2.58%.
[0035] It is preferred to control the size of the AlMnSi phase in the core material layer within the above range, which helps to improve the mechanical properties and anti-sagging performance of the aluminum alloy composite plate before and after brazing. It is preferred to control the size and area ratio of the Fe-containing second phase in the core material layer within the above range, which helps to further improve the formability and corrosion resistance of the aluminum alloy composite plate.
[0036] In another typical embodiment of the present application, a method for preparing the above-mentioned aluminum alloy composite plate is provided, and the preparation method comprises: step S1, heating and rolling the first skin material ingot, the core material ingot and the second skin material ingot independently in sequence to obtain the first skin material ingot layer, the core material ingot layer and the second skin material ingot layer, and stacking the first skin material ingot layer, the core material ingot layer and the second skin material ingot layer in sequence and performing composite rolling treatment to obtain a composite billet; step S2, preheating the composite billet, hot rough rolling and hot finish rolling in sequence to obtain a hot-rolled billet; and step S3, cold rolling, intermediate annealing and heat treatment of the hot-rolled billet in sequence. The aluminum alloy composite plate is obtained by annealing and secondary cold rolling; wherein the preheating process includes: heating the composite blank to 460-490°C at 30-80°C / h and then keeping it warm for 1-6h; the intermediate annealing is direct annealing of the blank after the first cold rolling or continuous intermediate annealing; the direct annealing process includes: heating the blank after the first cold rolling to 380-460°C at 20-90°C / h and then keeping it warm for 0.5-3h; the continuous intermediate annealing process includes: heating the blank after the first cold rolling to 400-480°C at 30-120°C / s and then keeping it warm for 60-240s, and then cooling it to below 100°C at 50-250°C / s.
[0037] The present application adopts a preheating treatment and intermediate annealing process of rapid heating, short-time high temperature or long-time insulation at medium and high temperature, which can precipitate more fine AlMnSi dispersed phases to the greatest extent, thereby improving the mechanical properties and anti-drooping performance of the aluminum alloy composite plate before and after brazing, and can improve the yield strength of the aluminum alloy composite plate after brazing by more than 20MPa compared with the prior art. The composite billet of the above-mentioned three-layer structure can be obtained by step S1, which is helpful for subsequent preheating treatment. The above-mentioned preheating treatment can control the size and number density of the AlMnSi dispersed phase, thereby improving the strength of the aluminum alloy composite plate, and at the same time lays a good organizational foundation for obtaining long strip-shaped large grains in the subsequent brazing process. Through hot rough rolling and hot finishing rolling processes, hot-rolled billets with more precise thickness and better plate shape can be obtained. It is helpful to regulate the grain size and distribution through one cold rolling and two cold rolling, thereby improving the brazing performance and anti-drooping performance of the aluminum alloy composite plate. The above direct annealing can promote the precipitation of AlTiZr dispersed phase and AlMnSi dispersed phase, thereby improving the tensile properties, anti-sagging properties and anti-corrosion properties of the aluminum alloy composite plate. The above continuous intermediate annealing can control the precipitation and growth of AlTiZr dispersed phase and AlMnSi dispersed phase, thereby meeting the basic conditions for the final organization of the finished aluminum alloy composite plate. Therefore, the high-strength and corrosion-resistant aluminum alloy composite plate prepared by the present invention through the coordinated optimization of alloy composition and processing technology has excellent mechanical properties, anti-sagging properties and corrosion resistance.
[0038] In order to further control the size and number density of the AlMnSi dispersed phase and obtain the expected target structure of long strips of large grains, in one embodiment of the present application, the preferred preheating process includes: heating the composite billet to 460-490°C at 40-60°C / h and then keeping it warm for 2-4h.
[0039] In order to further control the precipitation of AlTiZr dispersed phase and AlMnSi dispersed phase and improve the tensile properties, anti-sagging properties and anti-corrosion properties of the aluminum alloy composite plate, in one embodiment of the present application, the direct annealing process preferably includes: heating the blank after a single cold rolling to 400-460°C at 50-80°C / h and then keeping it warm for 0.5-3h; and / or, the continuous intermediate annealing process includes: heating the blank after a single cold rolling to 440-480°C at 40-100°C / s and then keeping it warm for 60-240s, and then cooling it to below 100°C at 100-200°C / s.
[0040] In one embodiment of the present application, the total processing rate of the first cold rolling is 80-90%, and / or the total processing rate of the second cold rolling is 10-25%.
[0041] It is preferred to control the total processing rate of the first cold rolling within the above range, which not only helps to promote the crushing of coarse compounds, thereby improving the ductility of the aluminum alloy composite plate, but also helps to promote the uniform distribution of the eutectic silicon phase in the skin layer, thereby facilitating the uniform distribution of the subsequent brazing liquid phase, thereby improving the brazing quality of the aluminum alloy composite plate. It is preferred to control the total processing rate of the second cold rolling within the above range, which helps to regulate the deformation energy storage, and combined with the control of the second phase distribution, it is conducive to the formation of elongated grains with appropriate aspect ratios during the brazing process of the aluminum alloy composite plate, so that the aluminum alloy composite plate has good brazing performance and anti-sagging performance.
[0042] In one embodiment of the present application, the above-mentioned step S1 also includes: independently melting, sawing and milling the skin material alloy and the core material alloy in sequence to obtain skin material ingots and core material ingots, respectively; wherein, during the melting and casting process, the skin material alloy is modified by antimony; and / or the single-sided milling amount of the milling surface is 15 to 20 mm, and the difference between the longitudinal and transverse milling amounts of the milling surface is ≤2 mm.
[0043] By performing the above treatment on the skin alloy and the core alloy, and controlling the single-side milling amount of the milling surface and the difference between the longitudinal and transverse thickness of the milling surface within the above range, it is helpful to perform better composite rolling on the skin ingot and the core ingot in the subsequent process. The use of antimony for modification treatment not only helps to refine the size of eutectic silicon, but also helps to reduce the formation of welding defects in the aluminum alloy composite plate during high-temperature brazing, thereby helping to improve the corrosion resistance of the composite plate.
[0044] In one embodiment of the present application, in the above-mentioned step S1, a steel belt is used to fix the stacked structural member in which the first skin material ingot layer, the core material ingot layer and the second skin material ingot layer are stacked in sequence for composite rolling treatment, and the thickness ratio of the first skin material ingot layer, the core material ingot layer and the second skin material ingot layer is 1:8~10:1; and / or, the widths of the first skin material ingot layer and the second skin material ingot layer are each independently greater than the width of the core material ingot layer, and the difference between the widths of the first skin material ingot layer and the second skin material ingot layer and the width of the core material ingot layer has a tolerance of 10~40mm.
[0045] Before the composite rolling treatment, the skin material ingot and the core material ingot are independently heated and rolled, which helps to regulate the width of the first skin material ingot layer and the second skin material ingot layer to have a tolerance of the difference from the width of the core material ingot layer within the above range, which helps to facilitate the subsequent composite rolling treatment; the stacked structural parts are fixed with steel strips for composite rolling, and the thickness ratio of the first skin material ingot layer, the core material ingot layer and the second skin material ingot layer is preferably controlled within the above range, which helps to improve the stability of the composite structure of each layer of the composite billet.
[0046] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.
[0047] Example 1
[0048] In terms of mass percentage, the raw materials of the core alloy include the following elements: 0.35% Si element, 0.3% Cu element, 0.15% Mg element, 0.3% Fe element, 1.55% Mn element, the sum of the mass contents of Ti element and Zr element is 0.2%, and the balance is Al element;
[0049] In terms of mass percentage, the raw materials of the leather alloy include the following elements: 10.5% of Si element, 0.8% of Fe element, 1.5% of Mg element, 0.15% of Zn element, 0.1% of Bi element, and the balance is Al element.
[0050] The above skin material alloy and core material alloy are independently melt-cast, sawed and milled in sequence to obtain the first skin material ingot, the second skin material ingot and the core material ingot respectively, and then independently heated and rolled to obtain the first skin material ingot layer, the core material ingot layer and the second skin material ingot layer, and the first skin material ingot layer, the core material ingot layer and the second skin material ingot layer are stacked in sequence to obtain a stacked structure, and the stacked structure is fixed with a steel belt for composite rolling treatment to obtain a composite billet; wherein, the skin material alloy is modified by antimony during melting and casting, the single-sided milling amount of the milling surface is 15mm, and the difference between the longitudinal and transverse milling amounts of the milling surface is 2mm. The widths of the first skin material ingot layer and the second skin material ingot layer are independently greater than the width of the core material ingot layer, and the tolerance of the difference between the widths of the first skin material ingot layer and the second skin material ingot layer and the width of the core material ingot layer is 10mm. The thickness ratio of the first skin material ingot layer, the core material ingot layer and the second skin material ingot layer is 1:10:1.
[0051] The composite billet was heated to 460°C at a rate of 40°C / h and kept warm for 2h for preheating treatment, followed by hot rough rolling and hot finish rolling. The rolling rate of hot rough rolling was 90%, and the rolling rate of hot finish rolling was 83%, obtaining a hot rolled billet with a thickness of 6mm.
[0052] The hot-rolled billet is subjected to a cold rolling with a total processing rate of 80%. The billet is then heated to 400°C at a rate of 60°C / h and kept warm for 1.5h for intermediate annealing. Finally, a secondary cold rolling is performed with a total processing rate of 15%, thereby obtaining an aluminum alloy composite plate with a thickness of 0.6mm.
[0053] Example 2
[0054] In terms of mass percentage, the raw materials of the core alloy include the following elements: 0.5% Si element, 0.4% Cu element, 0.2% Mg element, 0.4% Fe element, 1.65% Mn element, the sum of the mass contents of Ti element and Zr element is 0.25%, and the balance is Al element;
[0055] In terms of mass percentage, the raw materials of the leather alloy include the following elements: 11% Si element, 0.8% Fe element, 1.6% Mg element, 0.18% Zn element, 0.12% Bi element, and the balance is Al element.
[0056] The above skin material alloy and core material alloy are independently melt-cast, sawed and milled in sequence to obtain the first skin material ingot, the second skin material ingot and the core material ingot respectively, and then independently heated and rolled to obtain the first skin material ingot layer, the core material ingot layer and the second skin material ingot layer, and the first skin material ingot layer, the core material ingot layer and the second skin material ingot layer are stacked in sequence to obtain a stacked structure, and the stacked structure is fixed with a steel belt for composite rolling treatment to obtain a composite billet; wherein, the skin material alloy is modified by antimony during melting and casting, the single-sided milling amount of the milling surface is 18mm, and the difference between the longitudinal and transverse milling amounts of the milling surface is 1.5mm. The widths of the first skin material ingot layer and the second skin material ingot layer are independently greater than the width of the core material ingot layer, and the difference between the widths of the first skin material ingot layer and the second skin material ingot layer and the width of the core material ingot layer has a tolerance of 25mm. The thickness ratio of the first skin material ingot layer, the core material ingot layer and the second skin material ingot layer is 1:10:1.
[0057] The composite billet was heated to 470°C at a rate of 50°C / h and kept warm for 3h for preheating treatment, followed by hot rough rolling and hot finish rolling. The rolling rate of hot rough rolling was 90%, and the rolling rate of hot finish rolling was 83%, obtaining a hot rolled billet with a thickness of 6mm.
[0058] The hot-rolled billet is subjected to a cold rolling with a total processing rate of 85%. The billet is then heated to 420°C at a rate of 60°C / h and kept warm for 1.5h for intermediate annealing. Finally, a secondary cold rolling is performed with a total processing rate of 18%, thereby obtaining an aluminum alloy composite plate with a thickness of 0.6mm.
[0059] Example 3
[0060] In terms of mass percentage, the raw materials of the core alloy include the following elements: 0.5% Si element, 0.5% Cu element, 0.25% Mg element, 0.5% Fe element, 1.65% Mn element, the sum of the mass contents of Ti element and Zr element is 0.25%, and the balance is Al element;
[0061] In terms of mass percentage, the raw materials of the leather alloy include the following elements: 11% Si element, 0.8% Fe element, 1.6% Mg element, 0.2% Zn element, 0.14% Bi element, and the balance is Al element.
[0062] The above skin material alloy and core material alloy are independently melt-cast, sawed and milled in sequence to obtain the first skin material ingot, the second skin material ingot and the core material ingot respectively, and then independently heated and rolled to obtain the first skin material ingot layer, the core material ingot layer and the second skin material ingot layer, and the first skin material ingot layer, the core material ingot layer and the second skin material ingot layer are stacked in sequence to obtain a stacked structure, and the stacked structure is fixed with a steel belt for composite rolling treatment to obtain a composite billet; wherein, the skin material alloy is modified by antimony during melting and casting, the milling thickness of the milling surface is 20mm, and the difference between the longitudinal and transverse milling amounts of the milling surface is 1mm. The widths of the first skin material ingot layer and the second skin material ingot layer are independently greater than the width of the core material ingot layer, and the difference between the widths of the first skin material ingot layer and the second skin material ingot layer and the width of the core material ingot layer has a tolerance of 40mm. The thickness ratio of the first skin material ingot layer, the core material ingot layer and the second skin material ingot layer is 1:10:1.
[0063] The composite billet was heated to 480°C at a rate of 50°C / h and kept warm for 3h for preheating treatment, followed by hot rough rolling and hot finish rolling. The rolling rate of hot rough rolling was 90%, and the rolling rate of hot finish rolling was 83%, obtaining a hot rolled billet with a thickness of 6mm.
[0064] The hot-rolled billet is subjected to a cold rolling with a total processing rate of 85%. The billet is then heated to 460°C at a rate of 60°C / s and kept warm for 180s. It is then cooled to below 100°C at 150°C / s for intermediate annealing. Finally, a secondary cold rolling is performed with a total processing rate of 15% to obtain an aluminum alloy composite plate with a thickness of 0.6 mm.
[0065] Example 4
[0066] The difference from Example 1 is that in the core material layer, the total mass content of Mn element and Fe element is 1.85%, the mass ratio of Mn element to Fe element is 3:1, and finally an aluminum alloy composite plate is obtained.
[0067] Example 5
[0068] The difference from Example 1 is that in the core material layer, the total mass content of Mn element and Fe element is 1.85%, the mass ratio of Mn element to Fe element is 4:1, and finally an aluminum alloy composite plate is obtained.
[0069] Example 6
[0070] The difference from Example 1 is that in the core material layer, the total mass content of Mn element and Fe element is 1.85%, the mass ratio of Mn element to Fe element is 8:1, and finally an aluminum alloy composite plate is obtained.
[0071] Example 7
[0072] The difference from Example 1 is that in the core material layer, the total mass content of Mg element and Si element is 0.5%, and the mass ratio of Mg element to Si element is 3:10, and finally an aluminum alloy composite plate is obtained.
[0073] Example 8
[0074] The difference from Example 1 is that in the core material layer, the total mass content of Mg element and Si element is 0.5%, the mass ratio of Mg element to Si element is 8:10, and finally an aluminum alloy composite plate is obtained.
[0075] Example 9
[0076] The difference from Example 1 is that in the core material layer, the total mass content of Mg element and Si element is 0.5%, the mass ratio of Mg element to Si element is 6:5, and finally an aluminum alloy composite plate is obtained.
[0077] Example 10
[0078] The difference from Example 1 is that the preheating process includes: heating the composite blank to 490° C. at 30° C. / h and then keeping the temperature for 1 hour, and finally obtaining an aluminum alloy composite plate.
[0079] Embodiment 11
[0080] The difference from Example 1 is that the preheating process includes: heating the composite blank to 460° C. at 80° C. / h and then keeping the temperature for 6 hours, and finally obtaining an aluminum alloy composite plate.
[0081] Example 12
[0082] The difference from Example 1 is that after the first cold rolling, the billet is heated to 380° C. at a rate of 20° C. / h and then kept at that temperature for 3 h for intermediate annealing, thereby finally obtaining an aluminum alloy composite plate.
[0083] Embodiment 13
[0084] The difference from Example 1 is that after the first cold rolling, the billet is heated to 460° C. at a rate of 90° C. / h and then kept at that temperature for 0.5 h for intermediate annealing, thereby finally obtaining an aluminum alloy composite plate.
[0085] Embodiment 14
[0086] The difference from Example 1 is that after the first cold rolling, the billet is heated to 400°C at 30°C / s and then kept at that temperature for 240s, and then cooled to below 100°C at 50°C / s for intermediate annealing, and finally an aluminum alloy composite plate is obtained.
[0087] Embodiment 15
[0088] The difference from Example 1 is that after the first cold rolling, the billet is heated to 480°C at 120°C / s and then kept at that temperature for 60s, and then cooled to below 100°C at 250°C / s for intermediate annealing, and finally an aluminum alloy composite plate is obtained.
[0089] Example 16
[0090] The difference from Example 1 is that the total processing rate of one cold rolling is 90%, and an aluminum alloy composite plate is finally obtained.
[0091] Embodiment 17
[0092] The difference from Example 1 is that the total processing rate of the first cold rolling is 70%, and an aluminum alloy composite plate is finally obtained.
[0093] Embodiment 18
[0094] The difference from Example 1 is that the total processing rate of the secondary cold rolling is 25%, and an aluminum alloy composite plate is finally obtained.
[0095] Embodiment 19
[0096] The difference from Example 1 is that the total processing rate of the secondary cold rolling is 35%, and an aluminum alloy composite plate is finally obtained.
[0097] Comparative Example 1
[0098] In terms of mass percentage, the raw materials of the core alloy include the following elements: 0.15% Si element, 0.65% Fe element, 1.35% Mn element, the sum of the mass contents of Ti element and Zr element is 0.1%, and the balance is Al element;
[0099] In terms of mass percentage, the leather alloy includes the following elements: 11% Si element, 0.8% Fe element, 0.8% Mg element, and the balance is Al element.
[0100] The above skin material alloy and core material alloy are independently melt-cast, sawed and milled in sequence to obtain the first skin material ingot, the second skin material ingot and the core material ingot respectively, and then independently heated and rolled to obtain the first skin material ingot layer, the core material ingot layer and the second skin material ingot layer, and the first skin material ingot layer, the core material ingot layer and the second skin material ingot layer are stacked in sequence to obtain a stacked structure, and the stacked structure is fixed with a steel belt for composite rolling treatment to obtain a composite billet; wherein, the skin material alloy is modified by antimony during melting and casting, the single-sided milling amount of the milling surface is 15mm, and the difference between the longitudinal and transverse milling amounts of the milling surface is 2mm. The widths of the first skin material ingot layer and the second skin material ingot layer are independently greater than the width of the core material ingot layer, and the tolerance of the difference between the widths of the first skin material ingot layer and the second skin material ingot layer and the width of the core material ingot layer is 10mm. The thickness ratio of the first skin material ingot layer, the core material ingot layer and the second skin material ingot layer is 1:10:1.
[0101] The composite billet was heated to 430°C at a rate of 50°C / h and kept warm for 3h for preheating treatment, followed by hot rough rolling and hot finish rolling. The rolling rate of hot rough rolling was 90%, and the rolling rate of hot finish rolling was 83%, obtaining a hot rolled billet with a thickness of 6mm.
[0102] The hot-rolled billet is subjected to a cold rolling with a total processing rate of 75%. The billet is then heated to 460°C at a rate of 60°C / s and kept warm for 180s. It is then cooled to below 100°C at 150°C / s for intermediate annealing. Finally, a secondary cold rolling is performed with a total processing rate of 20%, thereby obtaining an aluminum alloy composite plate with a thickness of 0.6 mm.
[0103] Comparative Example 2
[0104] The difference from Example 1 is that the preheating process includes: heating the composite blank to 520° C. at 90° C. / h and then keeping the temperature for 7 hours, and finally obtaining an aluminum alloy composite plate.
[0105] Comparative Example 3
[0106] The difference from Example 1 is that after the first cold rolling, the billet is heated to 480° C. at 100° C. / h and then kept at that temperature for 4 hours for intermediate annealing, thereby finally obtaining an aluminum alloy composite plate.
[0107] Comparative Example 4
[0108] The difference from Example 1 is that after the first cold rolling, the billet is heated to 380°C at 25°C / s and then kept at that temperature for 30s, and then cooled to below 100°C at 40°C / s for intermediate annealing, and finally an aluminum alloy composite plate is obtained.
[0109] Test Method
[0110] Yield strength, tensile strength and elongation test: Tested in accordance with GB / T228.1-2021 "Metallic Materials-Tensile Test Part 1: Room Temperature Test Method".
[0111] Anti-sagging value test: heat the air furnace to the brazing temperature of 610℃, put the sample (sample width 15mm, free end length 50mm), wait for the furnace temperature to return to the brazing temperature and keep it warm for 10 minutes, then take it out of the furnace and air cool it, and calculate the sagging value of the sample.
[0112] The size of the AlMnSi phase in the core material layer, the size of the Fe-containing second phase in the core material layer, and the area ratio of the Fe-containing second phase were tested: After the sample was polished, it was observed and photographed under a metallographic microscope without corrosion, and then measured through IPP (Image-Pro-Plus) software to obtain the area ratio of the second phase and the dispersed phase in the core material.
[0113] Potential difference test: The potential difference between the diffusion layer and the skin layer formed after brazing of the aluminum alloy composite plate was tested by seawater acidification cyclic corrosion test (SWAAT) for 1680 hours using ASTM G85-02 A3 standard.
[0114] The aluminum alloy composite plates of the above examples and comparative examples were subjected to organizational characterization and performance testing. The test results are shown in Tables 1 and 2.
[0115] Table 1
[0116]
[0117]
[0118] Table 2
[0119]
[0120]
[0121] in, Figure 1 is a morphology of the Fe-containing second phase in the core material layer of the aluminum alloy composite plate in Example 1. Figure 1 It can be seen that the size distribution of the AlFeMnSi phase is uniform. Therefore, regulating the amount of compounds formed by Mn, Fe and Si can make the aluminum alloy composite plate have higher strength and corrosion resistance.
[0122] Figure 2 is a morphology diagram of the AlMnSi phase of the aluminum alloy composite plate in Example 1. Figure 2It can be seen that the AlMnSi phase has a small size and a large number density. Therefore, the preheating treatment and intermediate annealing process of rapid heating, high temperature for a short time or medium and high temperature for a long time can precipitate more fine AlMnSi phases to the greatest extent, thereby improving the mechanical properties and anti-sagging properties of the aluminum alloy composite plate before and after brazing.
[0123] Figure 3 is a grain morphology diagram of the aluminum alloy composite plate after brazing in Example 1. Figure 3 It can be seen that the core material of the aluminum alloy composite plate after brazing is a long strip-shaped large-grain structure, which makes it have good high-temperature mechanical properties and brazing anti-sagging performance.
[0124] Figure 4 This is a morphology of the Fe-containing second phase in the core layer of the aluminum alloy composite plate in Comparative Example 1. Figure 4 It can be seen that the size distribution of AlFeMnSi phase is not uniform.
[0125] Figure 5 is a morphology diagram of the AlMnSi phase of the aluminum alloy composite plate in Comparative Example 1. Figure 5 It can be seen that the size of the AlMnSi phase is larger and the number density is smaller.
[0126] Figure 6 This is a grain morphology diagram of the aluminum alloy composite plate after brazing in Comparative Example 1. Figure 6 It can be seen that the grains of the core material of the aluminum alloy composite plate are fine after brazing. Therefore, the anti-sagging performance of the aluminum alloy composite plate after brazing is poor.
[0127] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0128] The aluminum alloy composite plate of the present application includes a core material layer and a skin material layer stacked on both sides of the core material layer. The structural design can optimize the comprehensive performance of the aluminum alloy composite plate. In the core material layer: the added Si element, Fe element and Mn element can form AlFeMnSi series compounds, thereby playing a role in dispersion strengthening. At the same time, the Si element, Fe element and Mn element are solid-dissolved in the matrix and can improve the strength of the aluminum alloy composite plate through solid solution strengthening, and the content of the Si element is controlled within the above range, which can not only improve the strengthening effect, but also avoid the problems of melting and collapse of the aluminum alloy composite plate during brazing and intergranular corrosion. Adding Mn and Fe elements can improve the forming performance and strength of the aluminum alloy composite plate. At the same time, controlling the content of the Fe element within the above range can improve the forming performance and corrosion resistance of the aluminum alloy composite plate. Adding Mg, Si and Cu elements helps to quickly cool the aluminum alloy composite plate after brazing and place it at room temperature to enable natural aging, thereby producing fine, dispersed Mg2Si phases and Al2CuMg phases. At the same time, a higher strength aluminum alloy composite plate can be obtained through the synergistic effect of solid solution strengthening and dispersion strengthening. The solid solution strengthening effect of adding Ti elements and Zr elements can improve the strength of the alloy, and at the same time, promote the generation of fine dispersed Al3Ti precipitation phase and Al3Zr precipitation phase, thereby further improving the strength of the alloy. In addition, the addition of Ti elements and Zr elements can promote the formation of coarse and long strip grains during brazing of aluminum alloy composite plates, thereby improving the anti-sagging performance of aluminum alloy composite plates; controlling the content of Ti elements in the above range can change the corrosion potential of the alloy, thereby improving the corrosion resistance of aluminum alloy composite plates. In each skin material layer: the added Bi element can not only increase the wettability of Si liquid phase to the surface of aluminum alloy material, but also promote the fluidity of Si liquid phase, thereby improving the welding performance of aluminum alloy composite plates. The low content of Bi element cannot achieve the performance of the above aluminum alloy composite plate. The high content of Bi element not only has limited effect on further improvement, but also leads to increased cost. Therefore, controlling the content of Bi element in the above range can take into account both effect and cost. Controlling the content of Zn element within the above range can reduce the corrosion potential of each skin material layer, so that the potential difference between the diffusion layer and the skin material layer formed after brazing of the aluminum alloy composite plate is ≥450mV, and the potential distribution of the diffusion layer is uniform and the driving force of galvanic corrosion is reduced, thereby improving the corrosion resistance of the aluminum alloy composite plate. Among them, the diffusion layer is a tissue layer formed by the mutual diffusion of alloy elements under the action of concentration gradient during the brazing process between the skin material and the core material. By coordinating and optimizing the above elements in the core material layer and each skin material layer, the mechanical properties, anti-sagging performance and corrosion resistance of the aluminum alloy composite plate can be comprehensively improved, so as to better meet the requirements of long-term operation of offshore wind turbines.
[0129] The above are only embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An aluminum alloy composite plate, characterized in that: The aluminum alloy composite plate comprises a core material layer and a skin material layer stacked on two opposite surfaces of the core material layer; In terms of mass percentage, the core material layer includes the following elements: 0.2-0.6% Si element, 0.3-0.6% Cu element, 0.1-0.3% Mg element, 0.2-0.6% Fe element, 1.4-1.8% Mn element, the sum of the mass contents of Ti element and Zr element is 0.15-0.4%, the total content of unavoidable impurities is ≤0.15%, the content of a single impurity is <0.05%, and the balance is Al element; In terms of mass percentage, each of the skin material layers comprises the following elements: 9.5-12.0% Si element, 0.6-1.0% Fe element, 1.4-1.8% Mg element, 0.05-0.25% Zn element, 0.08-0.2% Bi element, the total content of unavoidable impurities is ≤0.15%, the content of a single impurity is <0.05%, and the balance is Al element; The potential difference between the diffusion layer formed after brazing of the aluminum alloy composite plate and the skin material layer is ≥450mV; Before brazing the aluminum alloy composite plate, the aluminum alloy composite plate has a tensile strength of ≥220 MPa, a yield strength of ≥195 MPa, and an elongation of ≥5.5%; After the aluminum alloy composite plate is brazed, the yield strength of the aluminum alloy composite plate is ≥64.7 MPa, and the anti-sagging value is ≤4 mm.
2. The aluminum alloy composite plate according to claim 1, characterized in that: The core material layer comprises the following elements in percentage by mass: 0.3-0.5% Si, 0.4-0.6% Cu, 0.15-0.25% Mg, 0.2-0.4% Fe, 1.5-1.7% Mn, the sum of the mass contents of Ti and Zr is 0.2-0.3%, the total content of unavoidable impurities is ≤0.15%, the content of a single impurity is <0.05%, and the balance is Al; In terms of mass percentage, each of the skin material layers includes the following elements: 10-11.5% Si element, 0.6-0.8% Fe element, 1.45-1.65% Mg element, 0.1-0.2% Zn element, 0.1-0.15% Bi element, the total content of inevitable impurities is ≤0.15%, the content of a single impurity is <0.05%, and the balance is Al element.
3. The aluminum alloy composite plate according to claim 1 or 2, characterized in that: In the core material layer, the mass ratio of the Mn element to the Fe element is 4 to 6:1, and / or the mass ratio of the Mg element to the Si element is 3 to 8:
10.
4. The aluminum alloy composite plate according to any one of claims 1 to 3, characterized in that: The size of the AlMnSi dispersed phase in the core material layer is 100-200 nm; the size of the Fe-containing second phase in the core material layer is controlled to be 1-10 μm, and the area proportion of the Fe-containing second phase in the core material layer is 1.6-2.58%.
5. A method for preparing the aluminum alloy composite plate according to any one of claims 1 to 4, characterized in that: The preparation method comprises: Step S1, heating and rolling the first skin material ingot, the core material ingot and the second skin material ingot independently and sequentially to obtain a first skin material ingot layer, a core material ingot layer and a second skin material ingot layer, and sequentially stacking the first skin material ingot layer, the core material ingot layer and the second skin material ingot layer and performing a composite rolling process to obtain a composite billet; Step S2, sequentially performing preheating treatment, hot rough rolling and hot finish rolling on the composite billet to obtain a hot rolled billet; and Step S3, sequentially performing primary cold rolling, intermediate annealing and secondary cold rolling on the hot-rolled billet to obtain the aluminum alloy composite plate; The preheating process includes: heating the composite blank to 460-490°C at 30-80°C / h and then keeping the temperature for 1-6h; The intermediate annealing is direct annealing of the blank after one cold rolling or continuous intermediate annealing; The direct annealing process comprises: heating the blank after the primary cold rolling to 380-460° C. at 20-90° C. / h and then keeping the temperature for 0.5-3h; The continuous intermediate annealing process comprises: heating the blank after the primary cold rolling to 400-480°C at 30-120°C / s, keeping the temperature for 60-240s, and then cooling to below 100°C at 50-250°C / s.
6. The preparation method according to claim 5, characterized in that: The preheating process includes: heating the composite blank to 460-490° C. at a rate of 40-60° C. / h and then keeping the temperature for 2-4 hours.
7. The preparation method according to claim 5 or 6, characterized in that: The direct annealing process includes: heating the blank after the first cold rolling to 400-460°C at 50-80°C / h and then keeping it warm for 0.5-3h; and / or, the continuous intermediate annealing process includes: heating the blank after the first cold rolling to 440-480°C at 40-100°C / s and then keeping it warm for 60-240s, and then cooling it to below 100°C at 100-200°C / s.
8. The preparation method according to any one of claims 5 to 7, characterized in that: The total processing rate of the first cold rolling is 80-90%, and / or the total processing rate of the second cold rolling is 10-25%.
9. The preparation method according to any one of claims 5 to 8, characterized in that: The step S1 further comprises: independently and sequentially melting, sawing and milling the skin material alloy and the core material alloy to obtain skin material ingots and core material ingots respectively; Wherein, during the melting and casting process, antimony is used to modify the skin alloy; And / or, the single-side milling amount of the milled surface is 15-20 mm, and the difference between the longitudinal and transverse milling amounts of the milled surface is ≤2 mm.
10. The preparation method according to any one of claims 5 to 9, characterized in that: In the step S1, a steel belt is used to fix the laminated structure obtained by sequentially laminating the first skin material ingot layer, the core material ingot layer and the second skin material ingot layer to perform the composite rolling process; The thickness ratio of the first skin material ingot layer, the core material ingot layer and the second skin material ingot layer is 1:8 to 10:1; And / or, the widths of the first skin material ingot layer and the second skin material ingot layer are each independently greater than the width of the core material ingot layer, and the tolerance of the difference between the widths of the first skin material ingot layer and the second skin material ingot layer and the width of the core material ingot layer is 10 to 40 mm.
Citation Information
Patent Citations
A method for preparing a three-layer composite plate of 308 aluminum alloy for vacuum brazing.
CN110947762B
Aluminum alloy composite material for brazing and manufacturing method thereof
CN115771311A
High-sag-resistance brazing composite aluminum alloy foil for heat exchanger
CN102676884A
Aluminum alloy composite sheet material for soldered honeycomb panel, and manufacturing method thereof
WO2018058306A1
